2013
DOI: 10.1523/jneurosci.2638-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Speed-Dependent Contribution of Callosal Pathways to Ipsilateral Movements

Abstract: Transcallosal inhibitory interactions between primary motor cortices are important to suppress unintended movements in a resting limb during voluntary activation of the contralateral limb. The functional contribution of transcallosal inhibition targeting the voluntary active limb remains unknown. Using transcranial magnetic stimulation, we examined transcallosal inhibition [by measuring interhemispheric inhibition (IHI) and the ipsilateral silent period (iSP)] in the preparatory and execution phases of isotoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…A recent imaging study found increased i M1 activation with the demand for precision during a pointing task suggesting that the involvement of i M1 relates to task difficulty (Buetefisch et al ., ). Also, a lesion to the i M1 caused by cerebral infarction impairs fine motor control of the hand (Parkin, ), whereas temporarily disrupting iM1 with repetitive TMS in able‐bodied subjects can impair execution of complex piano sequences (Chen et al ., ) and alter timing of muscle recruitment probably through transcallosal influences (Davare et al ., ; Tazoe & Perez, ). This interpretation is supported by the sparse ipsilateral corticospinal connections seen in non‐human primates (Soteropoulos et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent imaging study found increased i M1 activation with the demand for precision during a pointing task suggesting that the involvement of i M1 relates to task difficulty (Buetefisch et al ., ). Also, a lesion to the i M1 caused by cerebral infarction impairs fine motor control of the hand (Parkin, ), whereas temporarily disrupting iM1 with repetitive TMS in able‐bodied subjects can impair execution of complex piano sequences (Chen et al ., ) and alter timing of muscle recruitment probably through transcallosal influences (Davare et al ., ; Tazoe & Perez, ). This interpretation is supported by the sparse ipsilateral corticospinal connections seen in non‐human primates (Soteropoulos et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, it might be that a functional role of the decreased transcallosal inhibition can be observed in a time-specific motor event like movement initiation. Transcallosal inhibition is gradually decreased according to the time course of movement initiation [50] , [51] . Therefore, a sustained reduction of transcallosal inhibition could contribute to such a situation of motor performance rather than a static enhancement of corticospinal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the difference in EMG activity it has recently been shown that level of EMG does not influence the degree of inhibition. 51 Results are reported as ISP ratio, which is defined as the Contralesional to Ipsilesional iSP/Ipsilesional to Contralesional iSP. The subject shown had an iSP ratio of .75.…”
Section: Figurementioning
confidence: 99%